2009
DOI: 10.1152/ajpheart.00595.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of VASP phosphorylation in cardiac myocytes: differential regulation by cyclic nucleotides and modulation of protein expression in diabetic and hypertrophic heart

Abstract: Sartoretto JL, Jin BY, Bauer M, Gertler FB, Liao R, Michel T. Regulation of VASP phosphorylation in cardiac myocytes: differential regulation by cyclic nucleotides and modulation of protein expression in diabetic and hypertrophic heart. Am J Physiol Heart Circ Physiol 297: H1697-H1710, 2009. First published September 4, 2009 doi:10.1152/ajpheart.00595.2009.-Vasodilator-stimulated phosphoprotein (VASP) is a major substrate for cyclic nucleotide-dependent kinases that has been implicated in cardiac pathology, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…3A, preincubation of cardiac myocytes with PEG-catalase abrogates subsequent Ang-II-promoted increase in eNOS phosphorylation at residues serine 1177 and serine 633. We and others previously showed that the β-adrenergic agonist isoproterenol promotes eNOS phosphorylation in cardiac myocytes (8,22). Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…3A, preincubation of cardiac myocytes with PEG-catalase abrogates subsequent Ang-II-promoted increase in eNOS phosphorylation at residues serine 1177 and serine 633. We and others previously showed that the β-adrenergic agonist isoproterenol promotes eNOS phosphorylation in cardiac myocytes (8,22). Fig.…”
Section: Resultsmentioning
confidence: 85%
“…The heart was quickly removed from the chest and retrogradely perfused through the aorta as described (39). Cardiac myocyte isolation methods followed the procedures as described (39), with minor modifications as we have previously reported (22). In brief, enzymatic digestion was initiated by adding collagenase type 2 to the cardiac perfusion solution, followed by the stepwise introduction of CaCl 2 , after which the heart tissue was minced and the cells were dispersed by trituration, following which the cardiac myocytes were allowed to settle, and then washed, pelleted, counted, and plated.…”
Section: Methodsmentioning
confidence: 99%
“…19 Concentrations of NOx (NOx = NO˙+ NO 2 + NO 3 ) were measured by using the previously reported vanadium reduction method. 9 Our results showed that young adult hearts had a low basal NOx, and aged hearts had a markedly increased basal NOx compared to young adult hearts (Fig.…”
Section: Production Of Onoomentioning
confidence: 99%
“…Detection of a high degree of autophosphorylation on the overexpressed PKD1 and PKD2 using a phosphospecific antibody (against PKD-pSer916), which reflects the activation state of both isoforms (Matthews et al, 2000), indicated that they were active when transfected into BAECs. In addition, the increased appearance of vasodilatorstimulated phosphoprotein (VASP) phosphorylated at Ser239, a read-out for NO release (Sartoretto et al, 2009), suggested that eNOS phosphorylation on Ser1179 mediated by PKD1 and PKD2 resulted in enzymatic activation and increased NO synthesis. BAECs presented a basal level of eNOS Ser1179 phosphorylation, which indicated this particular site was already phosphorylated in endothelial cells by endogenous serine kinases, including PKD.…”
Section: +mentioning
confidence: 99%